An analysis of student's speaking difficulties in reporting a procedure text - Nurul hayati daely; Yenni Julia Ningsih; Melindah Harianja; Rahmawati; fitri dian ningsih Gea (Universitas Lancang Kuning, 2020)
Speaking skill is the skill that give us the ability to communicate effectively. The objective of the study were: (1) to find out the difficulties in reporting procedure text, (2) to find out the reason why do the students feel difficulties in reporting the procedure text, (3) to analysis why the difficulties occur at the studentsspeaking in reporting a procedure text.The population was all of the students first grade X-IPA of SMA Methodist 7 Medan 2019/2020 academic year. The sample of this research was the first grade X IPA consist 29 students in the class. The purpose of this study was to determine student knowledge in the text of the reporting procedure to determine student difficulties in the text of the reporting procedure. This researchers used qualitative method to know and examine the difficulties that occur and strive to resolve existing problems in speaking. From the results of research that has been conducted research, researchers found several that are classified through analysis, namly related to students difficulty in speaking, lack of vocabulary used, lack of pronouncation, and lack of knowledge about listening. And researchers used five aspects in giving scored namly Fluency, pronouncation, Accuracy, Clarity, and Performance skill.The researchers concluded in the other words that there was a significant analysis of students difficulties in reporting procedure text. It is suggested that English Teachers must practicing they speaking skill.